Forrestopius Gauld & Sithole, 2002 (Hymenoptera: Ichneumonidae: Metopiinae) in South America - Alvarado, Mabel; Palacio, Edgard (Zootaxa, 2021)
The South American species of Forrestopius Gauld & Sithole, 2002 (Ichneumonidae: Metopiinae) are revised and the genus is redescribed. Eight species from Colombia, Ecuador, Perú, and Venezuela are described as new: F. auguratricis sp. nov., F. jumandi sp. nov., F. nasutus sp. nov., F. otavalo sp. nov., F. petiolatus sp. nov., F. runasimi sp. nov., F. wankawillka sp. nov., and F. yungas sp. nov. An illustrated identification key to all species of the genus is provided. As well, F. larryi Gauld & Sithole, 2002 is transferred to the genus Leurus.